Pengaruh Penggunaan Gadget terhadap Pembentukan Nilai Pendidikan Agama di MI Muhammadiyah Bolon - Mujahid, Kasori; Sayidah, Aminatus (Lembaga Yasin AlSys, 2025)
This article discusses the influence of gadget use on the formation of religious education values ​​in schools. In today's digital era, the use of gadgets by students is increasingly widespread, which can have a significant impact on the learning process, including the formation of character and religious values. This study examines the positive and negative impacts of gadget use on students' understanding and appreciation of religious values ​​taught in schools. Through a qualitative approach and data analysis from observations and interviews with students, teachers, and parents, it was found that uncontrolled gadget use can distract students from religious education materials, affect their social attitudes, and reduce the quality of their interactions in a religious context. On the other hand, with proper utilization, gadgets can be an effective tool to support religious learning, such as through access to religious education applications and relevant digital materials. This article suggests the need for stricter regulations regarding the use of gadgets at home and the importance of the role of teachers and parents in providing guidance to students to use technology wisely in the context of forming religious education values.